(untitled) - Tille, Patricia M. (St. Louis, 2017)
Perfect your lab skills with the gold standard in microbiology! Serving as both the #1 bench reference for practicing microbiologists and as a favorite text for students in clinical laboratory science programs, Bailey & Scott’s Diagnostic Microbiology, 14th Edition covers all the topical information and critical thinking practice you need for effective laboratory testing. This new edition also features hundreds step-by-step procedures, updated visuals, new case studies, and new material on the latest trends and equipment in clinical microbiology ― including automation, automated streaking, MALDI-TOF, and incubator microscopes. It’s everything you need to get quality lab results in class and in clinical practice!
Keywords: Kỹ thuật vi sinh,Microbiological techniques